EFL TEACHERS’ WRITING STRATEGIES IN ACADEMIC WRITING WHILE PURSUING A MASTER’S DEGREE ABOARD - Wijayanti, Sheirly Octaviantoro Ayu; Mukminatien, Nur; Sujiatmoko, Ahmad Heki (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
The use of English for adult L2 writers encountered significant challenges in an English-mediated environment. This phenomenon is experienced by EFL teachers while pursuing a Master’s degree abroad. The necessity of challenges and the lack of writing strategies may highlight the obstacles to writing productivity. Therefore, identifying the challenges and effective writing strategies is needed to achieve the goal of writing a thesis. This study used a qualitative narrative inquiry, with in-depth interviews, and focused on 3 Indonesian participants who studied abroad. The findings showed several challenges faced by participants, including academic and non-academic challenges. Academic challenge covers language and content challenge, including problems in grammar, academic style, vocabulary, finding a topic, and novelty, as well as non-academic challenge, including issues in supervisor relationship, time management, mental and emotional pressure. Also, four strategies are applied: cognitive, metacognitive, affective, and social. This research may guide future Master’s students on the importance of specific writing strategies in academic writing and may highlight effective English teaching and impact future international writing publications.